Do Cause-Related Marketing Affect Purchase Intention and Brand Loyalty of Muslim Consumers on Halal Foods? - Timur, Yan Putra; Sari, Dyah Permata (AFEBI Islamic Finance and Economic Review, 2023)
The objective of this study is to examine the impact of Cause-Related Marketing (CRM) strategy on the Consumer Purchase Intention (CPI) and Brand Loyalty (BL) of Muslim customers towards halal food products. The researchers utilised religiosity (RG) variable to investigate the moderating impact on factors associated with Muslim customers' marketing and purchasing intentions towards halal food. This research employs a quantitative approach, utilising the PLS-SEM evaluation model. The sample consisted of 200 individuals who identified as Muslim and were between the ages of 17 and 65. The study findings revealed that CRM had a positive and significant effect on both CPI and BL towards halal food products. In addition, the variable of BL significantly and positively affects the CPI of halal food. The researchers discovered varying outcomes for the RG variable. It was observed to have a positive moderating impact on the relationship between CRM and CPI, although this effect was not statistically significant. CRM Strategy is a strategic approach that yields favourable outcomes and advantages for consumers, companies, and receivers of donations. However, marketers must be attentive to the execution of CRM strategy. Several research have discovered that implementing this method leads to negative consequences, including increased scepticism and less warm glow effect among participating consumers. Keywords: Cause-Related Marketing, Consumer Purchase Intention, Halal Food, Brand Loyalty, Religiousity.